Medicinal uses, phytochemistry, and pharmacological properties of Piper aduncum L. - Muhammad Taher,; Mohamad Shahreen Amri,; Deny Susanti,; Muhammad Badri Abdul Kudos,; Nur Fasya Ajda Md Nor,; Syukri, Yandi (Penerbit Universiti Kebangsaan Malaysia, 2020)
Piper aduncum L., commonly known as ‘spiked pepper’, has various uses in traditional medicine that include treating wounds, skin boils, infections, and diarrhoea. Its properties as an anti-parasitic, antimicrobial, insecticidal, antitumor, and anticancer agent indicates that it could have further therapeutic potential in treating infections and cancers. The aim of this review was to provide a comprehensive summary of the traditional uses, phytochemistry and pharmacological properties of P. aduncum. Data were collected from electronic databases from 1978 to 2019. The plant is traditionally used for treating diarrhoea in Peru and for its wound-healing properties in Brazil and Papua New Guinea. Phenolics, monoterpenes, sesquiterpenes, and chromene have been found in the P. aduncum plant, and these bioactive compounds contribute to its anti-parasitic, antimicrobial, insecticidal, antitumor, and anticancer properties. Several pharmacological activities of P. aduncum have been reported, most notably in the treatment of infectious diseases and cancer. However, information regarding its safety and efficacy in humans is lacki